Budaya Konsumerisme Mahasiswi UIN Antasari Banjarmasin di Bidang Fashion Keagamaan Perspektif Herbert Marcuse - Zamil, Mud; Syadzali, Ahmad; Hakim, Abdul (Fakultas Ushuluddin dan Humaniora UIN Antasari Banjarmasin, 2023)
This research focuses on consumerism culture among female students at Antasari State Islamic University Banjarmasin in the field of religious fashion. The expanding consumerism culture causes people to behave consumptively, making shopping irrational. The purpose of this research is to discover how consumptive behavior exists in female students, along with the reasons for the making of this consumptive behavior, using the respondents that the researchers were able to collect. This research is classified as a type of qualitative research with a concentration on field research. Herbert Marcuse's perspective on consumption culture among female students is used in this study. This study's core data came from interviews with female students and firsthand observation at Antasari State Islamic University Banjarmasin. According to the findings of this study, female students exhibit consumptive behavior toward religious fashion products in order to satisfy their desires. Female students' attitudes toward religious fashion lead to one-dimensional behavior, mainly purchasing. According to Herbert Marcuse, the orientation of female students purchasing religious fashion products can be seen as one-dimensional human characteristics, such as total administration in the marketplace, functional language in advertisements, erasing history in fashion trends, false needs, and image hegemony among female students.